2015
DOI: 10.17306/j.npt.2015.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Properties of fermented beverages prepared from goat milk with the use of thickening starter cultures

Abstract: Streszczenie. W ostatnich latach obserwuje się dynamiczny wzrost produkcji napojów fermentowanych z mleka krowiego i koziego. Dużą popularnością cieszą się napoje o gęstej konsystencji. Celem pracy było wytworzenie metodą termostatową napojów fermentowanych z mleka koziego z użyciem dwóch różnych kultur starterowych firmy Sacco, a także dokonanie oceny sensorycznej i fizyczno-chemicznej otrzymanych napojów. Badania wykonywano bezpośrednio po wyprodukowaniu oraz po 3, 7, 14 i 21 dniach przechowywania w warunkac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…lactis on the texture of fermented goat milks. In recent years, similar results have been obtained in fermented milks made of goat milk inoculated with relevant cultures and commercial probiotic cultures (Mituniewicz-Małek et al, 2013;Teichert et al, 2015). Domagała (2005) showed that the duration of storage has a significant effect on texture properties of fermented goat milk, and this has been confirmed by many authors (Karademir et al, 2002;Uysal et al, 2003;Salvador and Fiszman, 2004;Tratnik et al, 2006;Domagała and Wszołek, 2008) and by our study.…”
Section: Short Communication: Effect Of the Addition Of Bifidobacterisupporting
confidence: 90%
See 1 more Smart Citation
“…lactis on the texture of fermented goat milks. In recent years, similar results have been obtained in fermented milks made of goat milk inoculated with relevant cultures and commercial probiotic cultures (Mituniewicz-Małek et al, 2013;Teichert et al, 2015). Domagała (2005) showed that the duration of storage has a significant effect on texture properties of fermented goat milk, and this has been confirmed by many authors (Karademir et al, 2002;Uysal et al, 2003;Salvador and Fiszman, 2004;Tratnik et al, 2006;Domagała and Wszołek, 2008) and by our study.…”
Section: Short Communication: Effect Of the Addition Of Bifidobacterisupporting
confidence: 90%
“…The effect of cold storage on texture parameters of fermented goat milks was also observed by Mituniewicz-Małek et al (2013. A statistically significant effect of cold storage on cohesiveness was reported by Teichert et al (2015), who observed that cohesiveness in fermented goat milk inoculated with thickening cultures significantly decreased after only 2 wk of storage. A similar situation was observed for viscosity, whereas the hardness and consistency of fermented goat milk under study did not change significantly in cold storage.…”
Section: Short Communication: Effect Of the Addition Of Bifidobacterimentioning
confidence: 65%
“…However, Cais-Sokolińska and Pikul [2008] noted a significant deterioration in brightness of color during the subsequent weeks of storage. Teichert et al [2015] noted a significant increase in brightness of color in goat yoghurts on the 21 st day of cool storage.…”
Section: Effect Of Storage On Physicochemical Featuresmentioning
confidence: 95%
“…According to Cais Sokolińska and Pikula [2008], the microbiological activity of yogurt microflora leads to the changes in potential acidity of the clot, and thus cause physical changes in the clot, resulting in a difference in the color brightness and the degree of color saturation. According to the research by Cais-Sokolińska and Majcher [2009] and after Teichert et al [2015], the source of changes in color parameters during storage lays in the fact that the casein complex passes from the micelar state into a dispersed state. The colloidal casein-calcium complex disperses light and make the milk look white.…”
Section: Effect Of Storage On Physicochemical Featuresmentioning
confidence: 99%
“…The pH values of cow's yoghurts recorded in the present study were lower than the results obtained by Amal et al ( 2016 ), Cho et al ( 2020 ), and Dimitrellou et al ( 2020 ). Teichert et al ( 2015 ) showed that the pH of goat's yoghurt ranged from 4.61 to 4.63 depending on the bacterial cultures used in the experiment. Contrary results were obtained by Sigdel et al ( 2018 ), who reported that the addition of dried mulberry (9.6 mg % of vitamin C) to yoghurt significantly reduced the pH from 4.37 to 4.31.…”
Section: Resultsmentioning
confidence: 99%